2001
DOI: 10.1097/00003246-200109000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorochemical liquids modulate cell-mediated inflammatory responses

Abstract: At PFC concentrations comparable with those in blood during liquid ventilation, PFC liquids did not induce variables associated with inflammation. In the presence of high PFC concentrations, simulating the condition in which bronchoalveolar cells are exposed to PFC, monocytes may be induced by PFB to produce reactive oxygen species, and blood leukocytes induced by PFB to express CD11b and by PFD to secrete interleukin-8; the presence of either PFC attenuated tumor necrosis factor-alpha production after lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…Thereby, Obraztsov and co-workers (24) noted a linear relationship between the magnitude of inhibition and the lipid solubility of the individual PFC. Accordingly, other investigators also found cellular PFC effects that correlated with the agent's lipophilicity but were independent of density and vapor pressure otherwise (23,39). Perfluorohexane has relatively poor lipid solubility, about four times less than that of perfluorooctylbromide.…”
Section: Discussionmentioning
confidence: 97%
“…Thereby, Obraztsov and co-workers (24) noted a linear relationship between the magnitude of inhibition and the lipid solubility of the individual PFC. Accordingly, other investigators also found cellular PFC effects that correlated with the agent's lipophilicity but were independent of density and vapor pressure otherwise (23,39). Perfluorohexane has relatively poor lipid solubility, about four times less than that of perfluorooctylbromide.…”
Section: Discussionmentioning
confidence: 97%
“…However, recent trials did not show any clinical benefit for patients treated with PLV when compared with CMV. Some studies have focused on antiinflammatory effects of PLV (2,7,9,(25)(26)(27). Because suppression of the inflammatory response might interfere with lung defense in case of bacterial pneumonia, possible interactions between bacteria and fluorocarbons need to be investigated systematically before recommendations can be given for clinical use of PLV.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the major studies regarding liquid ventilation have focused on animal experiments or in vitro experiments with few clinical trials. Based on these animal studies and cell experiments, liquid ventilation holds promise to improve low pulmonary compliance and gas exchange in addition to reducing pulmonary inflammatory responses, and ultimately improving the prognosis of animals with ARDS (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the results of clinical randomized controlled trials (RCTs) and basic research have produced conflicting results, and the outlook of liquid ventilation has been disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients require endotracheal intubation and positive pressure ventilation (1,2) and account for millions of days spent in intensive care units (5). In recent years, treatments of ALI/ARDS with improved efficacy have been sought, and studies have indicated that liquid ventilation with perfluorocarbon (PFC) compounds is a promising therapeutic approach (6)(7)(8)(9)(10)(11)(12)(13)(14). PFC is of interest for the treatment of ALI/ARDS due to the unique physicochemical properties, such as high solubility for oxygen, and the anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation